DO POSITIVISMO AO NEOCONSTITUCIONALISMO: DESENVOLVIMENTOS DA TEORIA DO DIREITO POSITIVO - SANTOS, ARIANA B. D.; SULZBACH, CAMILA C.; VIEIRA, GUSTAVO O.; CARMO, JULIANA S. D.; ROSA, RUBIENA A. (Salão do Conhecimento, 2013)
Resumo